Growing up in North America: Child well-being in Canada, the United States, and México - Children in North America Project (Luxembourg Income Study (LIS), 2006)
The premise of the Children in North America Project lies in the kind of world we live in today, an increasingly interdependent, complex, and connected world. It is a small world where school children living in a desert state or a prairie province know all about a tsunami because of images of wreckage from a giant wave half a world away. As the globe shrinks, so too does North America. The continent that is shared by three nations, each with its own proud history, is becoming more economically, socially, and culturally integrated- through trade, investment, communications, human migration, education, travel, and cultural exchange. Children in the three nations are increasingly being exposed to similar consumer goods, media messages, and social trends. Moreover, for some children, increased economic ties imply drastic changes to their immediate surroundings and prospects - whether it is a child living in an American family without work because the local employer moved its operations to Mexico or a child living without a father in a Mexican town because many working-age men have left to seek jobs in the United States or Canada. The sheer scale of migration from Mexico to the United States and, to a lesser extent, to Canada is changing the face of the region and the lives of countless children. The Mexican-born population in the United States more than doubled between 1990 and 2000, going to over 9 million people, according to U.S. Census data. Remittances from Mexicans working in the United States to families back home amounted to over 16 billion U.S. dollars in 2004 (as estimated by the Central Bank of Mexico), roughly 1.5 percent of the country's GDP. Added together, the sums that migrants send back home surpass Mexico's revenues from tourism, foreign aid, and foreign direct investment. The Children in North America Project is exploring these new realities. It is building a new knowledge base about children across the continent. That knowledge base includes measures of child well-being and the local, national, and tri-national contexts or environments in which families live. These data tell the story of a diverse population of children characterized by profound differences in their well-being and security both within countries and across the region. Through this project, we hope to build a better understanding of how our children are faring and the opportunities and challenges that they face looking to the future. Our goal is to inspire and mobilize action to make the lives of all children in North America better, to ensure that no child is left behind.
Keywords: 330; Kinder; Soziale Lage; Lebensstandard; USA; Kanada; Mexiko